Idiopathic pendular nystagmus in cattle of Urmia district - A Araghi – Sooreh (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2011)
Idiopathic pendular nystagmus is a benign disorder of eye movement without visual or neurologic problem. This study was aimed to determine the occurance of pendular nystagmus in cattle of Urmia, Iran. A total of 375 cattle were examined at slaughterhouse of Urmia. All animals were selected from two sexes (male 40, female 335), four breeds (Holstein 108, Brown Swiss 49, native 65, crossbred 153) and four age  groups (yearlings 68, 2 years 124, 3 years 120, 4 years and above 63). In total, 3(0.8%) cases of pendular nystagmus were founded. No positive cases were seen in males and native cattle. There was no significant difference between sexes, breeds and age groups (p>0.05).